A kinetic model describing injury-burden in team sports - Fuller, C. W. (Sports Medicine, 2017)
Background: Injuries in team sports are normally characterised by the incidence, severity, and location and type of injuries sustained: these measures, however, do not provide an insight into the variable injury-burden experienced during a season. Injury burden varies according to the team`s match and training loads, the rate at which injuries are sustained and the time taken for these injuries to resolve. At the present time, this time-based variation of injury burden has not been modelled. Objectives: To develop a kinetic model describing the time-based injury burden experienced by teams in elite team sports and to demonstrate the model`s utility. Methods: Rates of injury were quantified using a large eight-season database of rugby injuries (5253) and exposure (60,085 player-match-hours) in English professional rugby. Rates of recovery from injury were quantified using time-to-recovery analysis of the injuries. Results: The kinetic model proposed for predicting a team`s time-based injury burden is based on a composite rate equation developed from the incidence of injury, a first-order rate of recovery from injury and the team`s playing load. The utility of the model was demonstrated by examining common scenarios encountered in elite rugby. Conclusions: The kinetic model developed describes and predicts the variable injury-burden arising from match play during a season of rugby union based on the incidence of match injuries, the rate of recovery from injury and the playing load. The model is equally applicable to other team sports and other scenarios.